Spatial and temporal dynamics of virus occurrence in two freshwater lakes captured through metagenomic analysis - Mohiuddin, Mohammad; Schellhorn, Herb (Frontiers in Microbiology, 2015)
Viruses are the most abundant microorganisms in the aquatic environment, yet the identification of viruses and assessing their diversity still remains a challenge. Here, we present a robust, routinely usable approach to identify viruses from two freshwater lakes of the lower Great Lakes region, Lake Ontario and Lake Erie. We collected water samples from six different beaches of these two lakes during the summer period of 2012 and 2013, and separated into three distinct fractions, namely a bacterial fraction, a virus like particle (VLP) fraction and a fraction of eDNA (environmental DNA). DNA extracted from all three fractions was sequenced and bioinformatic analyses of sequences revealed the presence of viruses from major viral families. The analyzed viral sequences were dominated by bacteriophage sequences, but also contained many plant and animal viruses. Within the context of this study, geographic location does not appear to have a major impact on viral abundance and diversity since virome composition of both lakes were similar. Comparative analyses between eDNA and viral fractions showed that eDNA can be used in combination with VLP fractions to identify viruses from the environment.